High natural permissivity of primary rabbit cells for HIV-1, with a virion infectivity defect in macrophages as the final replication barrier - Tervo, Hanna-Mari; Keppler, Oliver Till (Journal of virology, 2010)
An immunocompetent, permissive, small-animal model would be valuable for the study of human immunodeficiency virus type 1 (HIV-1) pathogenesis and for the testing of drug and vaccine candidates. However, the development of such a model has been hampered by the inability of primary rodent cells to efficiently support several steps of the HIV-1 replication cycle. Although transgenesis of the HIV receptor complex and human cyclin T1 have been beneficial, additional late-phase blocks prevent robust replication of HIV-1 in rodents and limit the range of in vivo applications. In this study, we explored the HIV-1 susceptibility of rabbit primary T cells and macrophages. Envelope-specific and coreceptor-dependent entry of HIV-1 was achieved by expressing human CD4 and CCR5. A block of HIV-1 DNA synthesis, likely mediated by TRIM5, was overcome by limited changes to the HIV-1 gag gene. Unlike with mice and rats, primary cells from rabbits supported the functions of the regulatory viral proteins Tat and Rev, Gag processing, and the release of HIV-1 particles at levels comparable to those in human cells. While HIV-1 produced by rabbit T cells was highly infectious, a macrophage-specific infectivity defect became manifest by a complex pattern of mutations in the viral genome, only part of which were deamination dependent. These results demonstrate a considerable natural HIV-1 permissivity of the rabbit species and suggest that receptor complex transgenesis combined with modifications in gag and possibly vif of HIV-1 to evade species-specific restriction factors might render lagomorphs fully permissive to infection by this pathogenic human lentivirus.